Die Dipteren-Fauna von Neuseeland als systematisches und tiergeographisches Problem. - Hennig, Willi (Contributions to Entomology = Beiträge zur Entomologie, 1960)
1. A compilation is given of all the known groups of Diptera which are distributed in Australia and New Zealand on the one hand and in South America on the other hand. - 2. Factors are studied which might support the assumption of an antarctic evolution centre or an antarctic migration route between Australia, New Zealand and South America. Such factors may especially be found in the systematic structure of the animal groups distributed in both these areals. - 3. Previous systematic study of the Dipterous groups distributed both in Australia/New Zealand and South America has proved unable to yield for any of these groups a pattern of phylogenetic relationships which could be regarded as an argument for an antarctic evolution centre or even an antarctic migration route. This holds good also for those groups frequently cited as paradigms of the type of distribution under discussion and ifced as proof of a former antarctic connection. - 4. On the other hand, the possibility cannot be denied that a more intimate study in some Dipterous groups might be able to yield such patterns of relationships. Those Dipterous groups in which such a possibility could exist are peculiarly referred to. - 5. The relationships of Diptera distributed over the antarctic islands are studied. None of them proved to belong to a Dipterous group which is in addition distributed only in Australia/New Zealand (or in one of these areals) and in South America. On the other hand the relationship of some of these antarctic species suggests that they should not be regarded as postglacial immigrants. - 6. Based upon the consideration that any animal group distributed over the Southern continents must have a sister group on the Northern continents the question is discus-sed which point of time can be fixed as terminus post quern non for the origin of animal groups distributed in Australia/New Zealand and South America. As an especially cautious solution there is stated the boundary between early and late tertiary (i. e. between oligocene and miocene). It might be, however, no mistake, if in phylogenetic systematics or genealogical trees the time of the origin of amber incluses (i. e. lower oligocene at the latest) is accepted as the lowest age of the groups simultaneously distributed in Australia/New Zealand and in South America.